Fizeau interferometer with binary phase Fresnel-zone plate reference for precision measurement of large convex lens. (November 2018) - Wei, Xiaohong; He, Yuhang; Liu, Zhengkun; Xu, Kaiyuan; Gao, Bo; Li, Qiang; Liu, Ang; Chai, Liqun
Highlights: A flexible and accurate method of obtaining precision transmission wavefront of large convex lens interferometrically using Fresnel zone plate was presented. A direct comparison of the Fresnel zone plate method measurement with results from a Fizeau interferometry method test shows excellent agreement. Measurement uncertainty analysis shows less than λ/10 accuracy for measuring the transmission wavefront of a sphere lens with 30.5 m focal length and Φ410 mm clear aperture. Abstract: A method of obtaining precision transmission wavefront of large convex lens interferometrically using binary Fresnel zone plate (FZP) was presented. We present the results from a set of experiments that demonstrate the accuracy, flexibility, and the simplicity of performing the FZP test. A direct comparison of the FZP measurement with results from a Fizeau interferometry method shows excellent agreement. Finally, measurement uncertainty of lens due to alignment error and FZP fabrication processes is analyzed. This resulting analysis shows less than λ/10 accuracy for measuring the transmission wavefront of a sphere lens with 31.25 m focal length and Φ410 mm clear aperture.